Probing transient and steady-state electronic response in topological and 2D materials - Liu, Jiayun (Nanyang Technological University, 2022)
Over the past half a century, technological advancement in electronics has progressed at breakneck speed. It has brought about powerful microprocessors which are ubiquitous in modern electronics. This advancement fueled by our ever-increasing demand for faster electronics gave rise to the doubling of computation power in these microprocessors every few years. This progress however cannot carry on forever as the transistors are approaching the quantum limit where problems like leakage current and heat dissipation are limiting the performance of microprocessors. Therefore, there is a search for alternative technologies for the next generation of electronics.